2006
DOI: 10.1159/000092709
|View full text |Cite
|
Sign up to set email alerts
|

Procaterol Upregulates Peroxisome Proliferator-Activated Receptor-γ Expression in Human Eosinophils

Abstract: Peroxisome proliferator-activated receptor-γ (PPARγ) is a nuclear receptor that regulates immune reaction. We have previously demonstrated that human eosinophils express PPARγ and that stimulation with a synthetic agonist for PPARγ attenuated the factor-induced eosinophil activations. However, the modulator of PPARγ expression in eosinophils has not yet been studied. In this study, we investigated the effect of procaterol, the synthetic β2-adrenoceptor agonist widely used as bronchodilators in asthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 59 publications
(42 reference statements)
3
8
0
Order By: Relevance
“…One explanation for this PPARγ up-regulation is the reflection of an inflammatory response, which is consistent with the findings of previous studies [30, 31]. However, the PPARγ expression in eosinophils was unaltered on stimulation with IL-5, which is a major eosinophil-activating cytokine that is produced abundantly at allergic inflammatory sites [26]; further, it showed no correlation with the activation marker CD25 or eosinophilic cationic proteins in serum [32]. Recent studies in our laboratory indicated that de novo synthesis of PPARγ was induced in human eosinophils by culturing them along with drugs such as β-adrenoceptor agonist or theophylline at therapeutic concentrations [26, 33].…”
Section: Eosinophils Express Pparγ: An Intracellular Target Of 15d-pgj2supporting
confidence: 90%
See 2 more Smart Citations
“…One explanation for this PPARγ up-regulation is the reflection of an inflammatory response, which is consistent with the findings of previous studies [30, 31]. However, the PPARγ expression in eosinophils was unaltered on stimulation with IL-5, which is a major eosinophil-activating cytokine that is produced abundantly at allergic inflammatory sites [26]; further, it showed no correlation with the activation marker CD25 or eosinophilic cationic proteins in serum [32]. Recent studies in our laboratory indicated that de novo synthesis of PPARγ was induced in human eosinophils by culturing them along with drugs such as β-adrenoceptor agonist or theophylline at therapeutic concentrations [26, 33].…”
Section: Eosinophils Express Pparγ: An Intracellular Target Of 15d-pgj2supporting
confidence: 90%
“…To date, three mammalian PPAR subtypes that are encoded by separate genes have been identified – α, β (also termed δ), and γ. PPARγ is expressed by human hemopoietic cells such as monocytes, macrophages, dendritic cells, lymphocytes, and mast cells [25]. Human peripheral blood eosinophils constitutively expressed PPARγ [25, 26] that is predominantly located in the cytosol [27]. It has been shown that PPARγ undergoes nuclear translocation upon ligand activation [28].…”
Section: Eosinophils Express Pparγ: An Intracellular Target Of 15d-pgj2mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the influence of estradiol on cell function was previously assigned exclusively to genomic reaction, it is known that estradiol activates the membrane form of ER and can rapidly induce intracellular cyclic AMP (cAMP) elevation [24]. Recently, we found that the bronchodilators theophylline and procaterol upregulated PPARγ mRNA and protein expression in eosinophils [15, 16]. Because the functions of these drugs are mediated through cAMP signaling, elevated cAMP in eosinophils might play a role in augmentation of PPARγ expression.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry was used for studying the protein expression of PPARγ as previously described [15, 16]. Purified eosinophils were washed twice with PBS and then permeabilized with FIX & PERM (Caltag Lab., San Francisco, Calif., USA).…”
Section: Methodsmentioning
confidence: 99%